Carbon180 in 2021 : new challenges for a new era - Isaacs, Andrew M.; Coromina, Natàlia Costa I. (London : The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business, 2022)
In 2020, Carbon180 moved to Washington DC to focus increasingly on policy change that would catalyze carbon removal. President Joe Biden's administration promised swift action to mitigate climate change. With Carbon180 releasing the first presidential transition book focused on carbon removal, the organization was poised to capitalize on its mission with politics on its side. However, optimism was tempered by realism about the limits of what could be achieved in Congress. Also, how receptive would US corporations be if green policies became legally enforceable? This case study is a continuation of "Carbon180: Choosing a Winning Strategy for Carbon Removal."
Description based on XML content.
Keywords: elektronické knihy; electronic books; Environmental policy -- United States -- Case studies; Environmental law -- United States -- Case studies; Sustainability -- Case studies